Nursing Interventions and Patient Recovery Rates: A Study in Tertiary Hospitals - Maria Graciela; Hildapia Raba (Magenta Journal De Healthymedi, 2025)
This study examined the relationship between nursing interventions and patient recovery rates in tertiary hospitals in Maluku, Indonesia. Using a quantitative correlational design, data were collected from 210 inpatients selected through stratified random sampling across medical, surgical, and intensive care units. Nursing interventions were categorized into clinical, educational, and psychosocial activities, while recovery rates were assessed through clinical progress indicators such as length of stay, complications, and discharge status. Data analysis using Pearson correlation and multiple regression revealed significant positive relationships between nursing interventions and patient recovery (r = 0.54, p < 0.001), with clinical interventions emerging as the strongest predictor (β = 0.38, p < 0.001). Variations in recovery outcomes across wards indicated that structured nursing practices contributed to higher recovery rates in surgical patients. The findings highlight that effective and contextually adapted nursing interventions play a strategic role in improving recovery outcomes, optimizing hospital performance, and strengthening healthcare systems in resource-limited regions. Strengthening professional competence, continuous training, and culturally responsive care is essential for enhancing recovery and ensuring sustainable health service delivery in Maluku’s tertiary hospitals.